Estimation of the Pumping Pressure from Concrete Composition Based on the Identified Tribological Parameters - Chanh-Trung Mai; El-Hadj Kadri; Tien-Tung Ngo; Abdelhak Kaci; Mustapha Riche (Advances in Materials Science and Engineering)
A new method is proposed to estimate pumping pressure based on concrete composition without experimental measurements. Previous studies show that the pumping pressure depends on the interface friction between concrete and the wall of the pumping pipes. This friction is determined by the thickness and the rheology of the boundary layer formed at the interface. The latter is mainly formed by water, cement, and fine sand particles which come from concrete. Hence, interface parameters, which are the viscous constant and the interface yield stress, are directly related to concrete composition. In this work, at the first time the interface yield stress model is suggested and validated thanks to an experimental database also carried out in this study with a precision of around 13%. Then, the pressure estimation method is proposed using the two models to calculate the interface parameters. The validation of the method is carried out basing on the comparison with real measurements on the building site. This method enables the calculation of the pumping pressure with a precision of around 15%.